1990
DOI: 10.1038/346448a0
|View full text |Cite
|
Sign up to set email alerts
|

Spatial structures in microtubular solutions requiring a sustained energy source

Abstract: Microtubules are believed to be the principal organizers of the cell interior. Cells respond to a variety of stimuli by modifying the spatial distribution of the microtubules. These effects are central to cell division and morphogenesis, and embryo development. During embryo development, macroscopic patterns are frequently observed. Here we report that microtubular solutions spontaneously form alternating white and dark stripes about 1 mm wide and 1 cm long. Small-angle neutron scattering measurements show tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
81
0
1

Year Published

1999
1999
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(83 citation statements)
references
References 21 publications
1
81
0
1
Order By: Relevance
“…Interestingly this domain formation occurred throughout the cell, even in the regions not exposed to X-rays. There is a slight resemblance with the spontaneous pattern formations from microtubules in oscillating assembly/disassembly conditions, but in that case the authors reported orientations of the different domains of 90° [Tabony and Job, 1990]. No further investigations on this interesting phenomenon have been performed yet.…”
Section: Figurementioning
confidence: 89%
“…Interestingly this domain formation occurred throughout the cell, even in the regions not exposed to X-rays. There is a slight resemblance with the spontaneous pattern formations from microtubules in oscillating assembly/disassembly conditions, but in that case the authors reported orientations of the different domains of 90° [Tabony and Job, 1990]. No further investigations on this interesting phenomenon have been performed yet.…”
Section: Figurementioning
confidence: 89%
“…(6b), we use analytical approximations for the length dependence of the microtubule distributions as described in Sec. V. This stable numerical scheme can be generalized in future work to an effective algorithm for dealing with microtubule polymerization in one and two spatial dimensions [26] in order to investigate spatial patterns occurring during polymerization of microtubules [10,24]. The respective extension of the amplitude equation may also lead to new interesting insights.…”
Section: Discussionmentioning
confidence: 99%
“…For appropriate reaction dynamics, in vitro preparations self-organise over a period of several hours to form stationary macroscopic patterns of microtubule orientation and concentration [22,30] . In spectrophotometer cells (40 x 10 x 1 mm), a series of equidistant (0.5 mm) stripes form.…”
Section: Transportmentioning
confidence: 99%
“…Under appropriate conditions the formation in vitro of microtubules shows this type of behaviour [22,23]. In these preparations, self-organisation also results in the collective transport and organisation of any colloidal and sub-cellular particles initially present in the reaction mixture [24].…”
Section: Introductionmentioning
confidence: 99%